Experimental Study on Frost Heave Behavior of Steel Fiber Improved Soil - Rongjian Shi; Feng Huang; Fengtian Yue; Zequn Hong; Yichen Li (Geofluids)
The incorporation of steel fibers into the natural soil is generally considered to be a novel and effective way to reduce the amount of frost heave induced by an artificial freezing process in underground engineering. In order to analyze the frost heave behavior of the steel fiber improved soil, a one-dimensional frost heave test under the open recharge system was conducted in this paper, focusing on the influence of steel fiber content, size, and soil properties. The results show that small amounts of steel fibers in the soil will not significantly affect the freezing process and temperature distribution, while the water-conducting properties of the steel fibers and the effect of limiting the ice lens growth can reduce the frost heave rate of the samples incorporated with 0.5% steel fibers by 26.93%. At the same time, the reduction effect of the frost heave rate increases linearly with the increase of steel fiber content and length but weakens with the increase of steel fiber diameter. In terms of soil property influence, the frost heave rate of the clay samples was reduced by 14.31% compared to the silt samples, while the water migration was reduced by 11.99%. In addition, the cementation of the steel fibers with the soil will also inhibit the growth of the ice lens and reduce the external water migration, thus significantly lowering the frost heave rate. The results can provide a reference for the research of the frost deformation of similar modified soils.